Pendampingan Komunitas Pengemis dalam Melestarikan Piwulang Kanjeng Sunan Drajat Lamongan - MIFTACHUL ULUM; Abdul Mun’im; Sholihuddin Sholihuddin (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
Raden Qosim or better known as Kanjeng Sunan Drajat, is present in our midst and has colored the lives of Indonesians, especially the city of Lamongan. Concern and wisdom are still felt today with the concept of Piwulang Wenehono ... Wenehono ... ..... Wenehono ...... This concept gives the meaning of the command to always give... give ... give ... ... and not asking. But in reality not all citizens are aware of and understand the implicit meanings in it, some people only take advantage and take advantage of tourist areas as part of a way to make a living regardless of the sustainability of the site of Sunan Drajat. Economic inequality is the key to dying for someone to throw themselves into a puddle of life that is not in accordance with religious norms, some people decide to become beggars. The decision to become a beggar is based on economic factors, compulsion and cultural factors of his ancestors. Beggars coloring in the world of religious tourism, regardless of whether this is appropriate or as part of helping people to do charity Raden Qosim, atau lebih dikenal sebagai Kanjeng Sunan Drajat, hadir di tengah-tengah kita dan telah mewarnai kehidupan orang Indonesia, khususnya kota Lamongan. Kepedulian dan kebijaksanaan masih terasa saat ini dengan konsep Piwulang Wenehono ... Wenehono .... ..... Wenehono ...... Konsep ini memberi arti perintah untuk selalu memberi..., memberi ... memberi ... ... dan bukan meminta. Tetapi pada kenyataannya tidak semua warga negara menyadari dan memahami makna implisit di dalamnya, sebagian orang hanya mengambil keuntungan dan memanfaat kawasan wisata sebagai bagian dari cara untuk mencari nafkah tanpa memperhatikan keberlangsungan situs Sunan Drajat. Kesenjangan ekonomi adalah kunci untuk mati bagi seseorang untuk melemparkan dirinya ke dalam kubangan kehidupan yang tidak sesuai dengan norma agama, sebagian orang memutuskan untuk menjadi pengemis. Keputusan menjadi pengemis didasari karena faktor ekonomi, keterpaksaan dan faktor budaya nenek moyangnya. Pengemis turut mewarnai di dunia wisata religi, tanpa memperdulikan apakah ini pantas atau sebagai bagian dari membantu orang untuk beramal